Linking social motivation with social skill: The role of emotion dysregulation in autism spectrum disorder. (August 2019) - Neuhaus, Emily; Webb, Sara J.; Bernier, Raphael A.
Abstract: Autism spectrum disorder (ASD) is associated with pervasive social deficits as well as marked emotion dysregulation across the life span. Decreased social motivation accounts in part for social difficulties, but factors moderating its influence are not fully understood. In this paper, we (a) characterize social and emotional functioning among children and adolescents with ASD, (b) explore contributions of social motivation and emotion dysregulation to social skill, and (c) consider biological sex and intellectual functioning as moderators of these associations. In a sample of 2, 079 children and adolescents with ASD from the Simons Simplex Collection, we document direct effects of social motivation, internalizing symptoms, aggression, attention problems, irritability, and self-injurious behavior on children's social skills. Furthermore, dysregulation in several domains moderated the association between social motivation and social skill, suggesting a blunting effect on social motivation in the context of emotional difficulties. Moreover, when considering only individuals with intellectual skills in the average range or higher, biological sex further moderated these associations. Findings add to our understanding of social–emotional processes in ASD, suggest emotion dysregulation as a target of intervention in the service of social skill improvements, and build on efforts to understand sources of individual difference that contribute to heterogeneity among individuals with ASD.